Content validation of a bodybuilding, diet and supplementary knowledge measurement instrument (Research, Society and Development, 2020)
This study aimed to elaborate and validate the content of an instrument to evaluate the knowledge about bodybuilding, diet and supplementation. This is a study in which a content validation protocol was applied to physical education and nutrition professionals to judge the items. For this, 25 multiple choice items were elaborated with four alternatives, with only one correct one. To evaluate the items by experts, we used an instrument developed by the author himself, the Content Validation Protocol (PVC), which was used as a way of analysis and judgment of the items for judges evaluating this research. The PVC was structured to analyze the clarity and the level of relevance of the items on a four-point likert scale, where the former was considered "not relevant" and the latter as "very relevant", this process was individualized by question. After being submitted to the experts and analyzed by the Content Validity Index (IVC), 22 items were validated and could be applied in future research.